Engineering mechanics : statics - Plesha, Michael E.; Gray, Gary L.; Costanzo, Francesco, 1964- (Boston : McGraw-Hill, 2010)
The authors present the fundamental concepts in a modern context using applications and pedagogical devices that connect with today's students. The text features a five-part problem-solving
Chapter 1 Introduction -- Chapter 2 Vectors: Force and Position -- Chapter 3 Equilibrium of Particles -- Chapter 4 Moment of a Force and Equivalent Force Systems -- Chapter 5 Equilibrium of Bodies -- Chapter 6 Structural Analysis and Machines -- Chapter 7 Centroids and Distributed Force Systems -- Chapter 8 Internal Forces -- Chapter 9 Friction -- Chapter 10 Moments of Inertia -- Appendix A Technical Writing -- Appendix B Answers to Selected Problems.
Includes index.
Keywords: Statics; Mechanics, Applied